Change trajectory and influencing factors of community-based elderly service demand among Chinese older residents: a latent growth modeling analysis on CHHLS data of 2008 - 2018 - Maomin JIANG; Aixian TU (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo investigate developmental trajectory and influencing factors of the demand for community-based elderly services among older residents during 2008 - 2018 in China for evidence-based improvement of elderly service system and promotion of healthy aging. MethodsThe data on 2 454 residents aged 65 years and above at baseline were collected from four waves of the Chinese Longitudinal Healthy Longevity Survey (CLHLS) conducted in 2008, 2011, 2014, and 2018. The demand for community-based elderly services was assessed using an 8-point scale, representing eight care service items that could potentially be provided by communities. Mplus 8.3 was utilized to construct a latent growth modeling (LGM). The unconditional least squares method was employed to assess the trajectory of changes in demand for community-based elderly services without covariates, while a conditional LGM with covariates was developed to analyze the trajectory of changes in the demand and its influencing factors among the elderly population in China from 2008 to 2018. ResultsThe mean overall scores for demand of community-based elderly services among surveyed elder residents in 2008, 2011, 2014, and 2018 were found to be 4.89 ± 2.27, 5.49 ± 1.94, 5.38 ± 2.06 and 5.38 ± 2.06 respectively with no significant difference observed between the yearly scores (P > 0.05). The results of the unconditional LGM analysis results indicate that the quadratic function LGM without constraints is the optimal model for fitting developmental trajectories of item-specific demand for community-based elderly services among older adults from 2008 to 2018. The initial demand was significantly greater than 0 (intercept = 4.91, P < 0.01). The constructed model revealed an upward trend from 2008 to 2011 (slope = 0.38, P < 0.01), followed by a downward trend from 2011 to 2018 (slope = - 0.12, P < 0.01). The results of conditional LGM analysis demonstrated that age (β = 0.026), intercept of marital status (β = 0.260), place of residence (β = - 0.567), and years of education (β = 0.224) significantly influenced the intercept of demand for community-based elderly services among older adults (all P < 0.05). Specifically, both age and years of education positively predicted slope 1 (β1 = 0.021, 0.018, all P < 0.05), while the predictions for slope 2 were not statistically significant (all P > 0.05). Moreover, both the intercept and slope of marital status positively predicted slope 1 (β1 = 0.118，0.021, all P < 0.05), as well as positively predicting slope 2 (β2 = 0.146，0.049, all P < 0.05). Additionally, place of residence had a positive predictive effect on slope 1 and slope 2 (β1 = 0.707，β2 = 0.046, all P < 0.05). ConclusionThe demand for community-based elderly services among elderly residents in China exhibited a non-linear growth trajectory from 2008 to 2018. There were variations in the initial level and rate of growth of this demand, which were influenced by factors such as age, marital status, place of residence, and years of education.